1997
DOI: 10.1021/ac961121d
|View full text |Cite
|
Sign up to set email alerts
|

Step-Scan FT-IR Spectroelectrochemical Analysis of Surface and Solution Species in the Ferricyanide/Ferrocyanide Redox Couple

Abstract: Fourier transform infrared (FT-IR) spectrometry adds complementary structural information to sensitive electroanalytical measurements. In this work, in situ, external reflection FT-IR techniques allowed for examination of interfacial electrochemical events through a thin-layer spectroelectrochemical cell in which a sinusoidally modulated potential was applied to the electrode. The infrared spectra of electrochemically modulated species were measured by a step-scan FT-IR spectrometer. The phasesensitive detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 27 publications
(40 reference statements)
2
42
1
Order By: Relevance
“…Although there are reports [37,[39][40][41][42] on single ferricyanide solution which indicate formation of PB on the electrode surface, in our preliminary experiments in different salts as supporting electrolyte we did not observe any adsorption. However, adsorption was observed only after potential was cycled over wider potential limits (À0.1 to +0.9 V) than usual (À0.1 to +0.6), i.e., the formation of PB by cyclic voltammetry was obtained in wider potential limits in KCl as supporting electrolyte.…”
Section: Resultscontrasting
confidence: 70%
See 1 more Smart Citation
“…Although there are reports [37,[39][40][41][42] on single ferricyanide solution which indicate formation of PB on the electrode surface, in our preliminary experiments in different salts as supporting electrolyte we did not observe any adsorption. However, adsorption was observed only after potential was cycled over wider potential limits (À0.1 to +0.9 V) than usual (À0.1 to +0.6), i.e., the formation of PB by cyclic voltammetry was obtained in wider potential limits in KCl as supporting electrolyte.…”
Section: Resultscontrasting
confidence: 70%
“…Under some particular working conditions [36][37][38][39], the FeðCNÞ 3À 6 =FeðCNÞ 4À 6 electron transfer reaction involves the generation of different compounds that often adsorbed on the electrode surface. These species have been identified as Prussian blue or related compounds [37,[39][40][41][42]. Yang et al [36] found that in a weak acidic medium (pH 3.6) of KH 2 PO 4 (0.1 M) -HCl, a thin film of PB is deposited on a gold electrode by using cyclic voltammetry between À0.2 and +0.6 V. They also reported that deposition can occur on platinum and glassy carbon electrodes but the rates were slow (and almost the same) in comparison with those on the gold substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the molecular specificity of UVvisible spectroscopy is not high enough. The use of FT-IR spectroscopy has also been examined for this purpose [87,88]. However, the relatively low sensitivity of infrared spectroscopy, the thin-layer structure of the electrochemical cell, and some other technical problems have prevented its practical use.…”
Section: A New Approach To Electrode Dynamicsmentioning
confidence: 99%
“…The infrared signatures of the ferri/ferrocyanide redox couple provide an excellent handle for measuring speciation as the CN stretching vibration blue shifts by $75 cm À1 upon reduction of the iron(III) complex [28][29][30]. Fig.…”
Section: Time and Spatial Resolved Studiesmentioning
confidence: 99%